Medication overuse headache and awareness - ISSI, Zeynep Tuncer; DURAN, Hayriye; KUŞ, Mehmet Emin; HELVACIOĞLU, Nil; ELLIDOKUZ, Hülya; ÖZTÜRK, Vesile (Arquivos de Neuro-Psiquiatria, 2021)
Background: Medication overuse headache (MOH) is the worsening of an underlying headache due to the overuse of its acute treatment. Unintentionally, healthcare professionals may contribute to this condition. Health professionals play an important role in preventing this increasingly frequent and difficult-to-treat condition. Objective: To investigate MOH awareness among physicians with headache through a survey conducted among medical doctors on our university campus. Methods: This was an observational cross-sectional study about MOH awareness. The total number of medical doctors working in the Dokuz Eylül University Health Campus was provided by the administrative unit. A total of 18 questions were prepared and administered on a voluntary basis to obtain information about MOH awareness. Results: A total of 312 medical doctors were surveyed, including 198 (63.5%) from internal medical sciences, 81 (26%) from surgical medical sciences, and 33 (10.5%) from basic medical sciences. Half of the physicians in our sample were unaware of MOH. Our results showed that awareness of MOH, was quite low even among medical doctors. Conclusions: MOH causes both labor and financial losses to countries and impairs the quality of life of patients. Preventing excessive use of medications by raising awareness among doctors is an important step to prevent the development of MOH.
Keywords: Headache Disorders; Headache Disorders, Secondary; Migraine Disorders; Awareness; Socioeconomic Factors